2021
DOI: 10.3390/molecules26154546
|View full text |Cite
|
Sign up to set email alerts
|

Induced Nematic Phase of New Synthesized Laterally Fluorinated Azo/Ester Derivatives

Abstract: A new series of laterally fluorinated mesomorphic compounds, namely 2-fluoro-4-((4-(alkyloxy)phenyl)diazenyl)phenyl 4-substitutedbenzoate (Inx) were prepared and evaluated for their mesophase behavior. The synthesized series constitutes five members that possess different terminally attached polar groups (X). Their molecular structures were confirmed by elemental analyses and both FT-IR and NMR spectroscopy. Examination of the prepared derivatives was conducted via experimental and theoretical tools. Mesomorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 75 publications
(68 reference statements)
0
13
0
Order By: Relevance
“…It could be concluded that the kind and the thermal stability of the formed phases facilitate the molecular space-filling due to the attached terminals that influence the physical geometrical parameters to enhance the intermolecular attractions between molecules. Moreover, the high electron density predicted for the carbonyl oxygen of -OCO-linkage together with the appreciable quantity recorded for that of -C=N-linkage, as reflected in Figure 5, suggests significant contribution of these linkages to the derivatives' polarizability, which is an important factor that increases the mesophase thermal stability of a compound [56,57].…”
Section: Mesomorphic Behaviormentioning
confidence: 93%
See 1 more Smart Citation
“…It could be concluded that the kind and the thermal stability of the formed phases facilitate the molecular space-filling due to the attached terminals that influence the physical geometrical parameters to enhance the intermolecular attractions between molecules. Moreover, the high electron density predicted for the carbonyl oxygen of -OCO-linkage together with the appreciable quantity recorded for that of -C=N-linkage, as reflected in Figure 5, suggests significant contribution of these linkages to the derivatives' polarizability, which is an important factor that increases the mesophase thermal stability of a compound [56,57].…”
Section: Mesomorphic Behaviormentioning
confidence: 93%
“…Figure 5, suggests significant contribution of these linkages to the derivatives' polarizability, which is an important factor that increases the mesophase thermal stability of a compound [56,57].…”
Section: Mesomorphic Behaviormentioning
confidence: 99%
“…A twist-bend nematic phase has been observed in several Schiff bases, low-molecularmass liquid crystals [17][18][19][20]. Recent studies have been conducted on syntheses and research activities in this area [8,[21][22][23][24][25]. On the other hand, a wide range of terminal substituents, such as small polar compact substituents and alkoxy chains, are employed [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The position and spatial orientation of fluorine atom further influence properties of nematogenic materials. The physical characteristics of the resulting liquid crystalline material, such as melting and phase transition temperatures, mesomorphic morphology, dipole moment, and dielectric anisotropy, were significantly influenced by the combination of the lateral fluorine atom’s small size and high polarity [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%